Paying for Performance: The Education Impacts of a Community College Scholarship Program for Low-Income Adults - Barrow, Lisa; Richburg-Hayes, Lashawn; Rouse, Cecilia Elena; Brock, Thomas (Journal of Labor Economics, 2014)
We evaluate the effect of performance-based incentive programs on educational outcomes for community college students from a random assignment experiment at three campuses. Incentive payments over 2 semesters were tied to meeting two conditions—enrolling at least half-time and maintaining a C or better grade point average. Eligibility increased the likelihood of enrolling in the second semester after random assignment and total number of credits earned. Over 2 years, program group students completed nearly 40% more credits. We find little evidence that program eligibility changed types of courses taken but some evidence of increased academic performance and effort.